PMM.29 A case report of Haemophagoctic Lymphohistiocytosis in Pregnancy. (9th June 2014) - Hodson, K; Marsden, P; Waugh, J
Abstract : Introduction: Haemophagoctic Lymphohistiocytosis (HLH) is a rare systemic haematological condition characterised by fever, cytopenia, liver dysfunction, hepatosplenomegaly and hyperferritinaemia. The very poor prognosis associated with HLH may be improved by early diagnosis and chemotherapy. There have been very few case reports of HLH in pregnancy. Case report: A 41-year-old woman was admitted at 23 + 4 weeks gestation with hepatic encephalopathy. She had had 4 previous CS. At 14 weeks she complained of cervical lymphadenopathy, tiredness and weight loss. Investigations included cervical lymph node, splenic and bone marrow biopsy. She was diagnosed with Kruger's syndrome, a benign self-limiting condition. From 17 weeks she became increasingly jaundiced and at 23 + 2 weeks she went into acute liver failure and was transferred to ITU at a tertiary centre. She had a trans-oesophageal liver biopsy, which showed haemophagoctic lymphohistiocytoisis (HLH). She had a classical CS and was delivered of a female infant weighing 380g. Chemotherapy was initiated and she later on had a bone marrow transplant, which appeared to help her condition. Unfortunately she had numerous complications and it became increasingly difficult to ventilate her. She died 4 months later. Discussion: HLH is rare and this case illustrates the need for early involvement of a tertiary centre in pregnant women with abnormal liver function where the diagnosis is uncertain. A liver biopsy would have afforded the option of termination of pregnancy or treatment at an earlier stage. Delivery was in a controlled manner avoiding the risk of abruption and aided managing her clinical condition.